Monitoring the HIV continuum of care in key populations across Europe and Central Asia. Issue 7 (8th May 2018) - Brown, AE; Attawell, K; Hales, D; Rice, BD; Pharris, A; Supervie, V; Van Beckhoven, D; Delpech, VC; An der Heiden, M; Marcus, U; Maly, M; Noori, T
Abstract : Objectives: The aim of the study was to measure and compare national continuum of HIV care estimates in Europe and Central Asia in three key subpopulations: men who have sex with men (MSM), people who inject drugs (PWID) and migrants. Methods: Responses to a 2016 European Centre for Disease Prevention and Control (ECDC) survey of 55 European and Central Asian countries were used to describe continuums of HIV care for the subpopulations. Data were analysed using three frameworks: Joint United Nations Programme on HIV/AIDS (UNAIDS) 90‐90‐90 targets; breakpoint analysis identifying reductions between adjacent continuum stages; quadrant analysis categorizing countries using 90% cut‐offs for continuum stages. Results: Overall, 29 of 48 countries reported national data for all HIV continuum stages (numbers living with HIV, diagnosed, receiving treatment and virally suppressed). Six countries reported all stages for MSM, seven for PWID and two for migrants. Thirty‐one countries did not report data for MSM (34 for PWID and 41 for migrants). In countries that provided key‐population data, overall, 63%, 40% and 41% of MSM, PWID and migrants living with HIV were virally suppressed, respectively (compared with 68%, 65% and 68% nationally, for countries reporting key‐population data). Variation was observed between countries, with higher outcomes in subpopulations in Western Europe compared with Eastern Europe and Central Asia. Conclusions: Few reporting countries can produce the continuum of HIV care for the three key populations. Where data are available, differences exist in outcomes between the general and key populations. While MSM broadly mirror national outcomes (in the West), PWID and migrants experience poorer treatment and viral suppression. Countries must develop continuum measures for key populations to identify and address inequalities.